Resting State BOLD Variability Is Linked to White Matter Vascular Burden in Healthy Aging but Not in Older Adults With Subjective Cognitive Decline - Scarapicchia, Vanessa; Garcia-Barrera, Mauricio; MacDonald, Stuart; Gawryluk, Jodie R. (Frontiers in Human Neuroscience, 2019)
Background: Alzheimer’s disease (AD) is the leading cause of dementia. A lack of curative treatments and a rapidly aging global population have amplified the need for early biomarkers of the disease process. Recent advances suggest that subjective cognitive decline (SCD) may be one of the earliest symptomatic markers of the AD cascade. Previous studies have identified changes in variability in the blood oxygen level dependent (BOLD) signal in patients with AD, with a possible association between BOLD variability and cerebrovascular factors in the aging brain. The objective of the current study was to determine whether changes in BOLD variability can be identified in individuals with SCD, and whether this signal may be associated with markers of cerebrovascular integrity in SCD and older adults without memory complaints. Method: Data were obtained from the Alzheimer's Disease Neuroimaging Initiative (ADNI) database from 19 participants with SCD and 19 similarly-aged controls. For each participant, a map of BOLD signal variability (SDBOLD) was computed as the standard deviation of the BOLD timeseries at each voxel. Group comparisons were performed to examine differences in resting state SDBOLD in SCD versus healthy controls. Relationships were then examined between participant SDBOLD maps and neuroimaging markers of white matter vascular infarcts in each group separately. Results: Between-group comparisons showed no significant differences in whole-brain SDBOLD in individuals with SCD and controls. In the healthy aging group, higher white matter hyperintensity (WMH) burden was associated with greater SDBOLD in right temporal regions (p <0.05), and lower scores on a measure of global executive functioning. These associations were not identified in individuals with SCD. Conclusion: The current study underscores previous evidence for a relationship between SDBOLD and white matter vascular infarcts in the healthy aging brain. The findings also provide evidence for a dissociable relationship between healthy aging and SCD, such that in healthy controls, increased WMH is associated with declines in executive function that is not observed in older adults who present with memory complaints. Further multimodal work is needed to better understand the contributions of vascular pathology to the BOLD signal, and its potential relationship with pathological aging.